Do Leniency Policies facilitate Collusion? Experimental Evidence - Holger Rau; Georg Clemens (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper experimentally analyzes the cartel coordination challenge induced by the discrimination of cartel ringleaders in leniency policies. Ringleaders often take a leading role in the coordination and formation of a cartel. A leniency policy which grants amnesty to all "whistleblowers" except for ringleaders may therefore reduce the incentive to become a ringleader and may disrupt cartel formation. We analyze discriminatory and non-discriminatory leniency policies in a multi-stage cartel formation experiment where multiple ringleaders may emerge. Although theory predicts that cartels will always be reported, whistleblowing rarely occurs. Paradoxically the discriminatory leniency policy induces more firms to become ringleaders, which ultimately facilitates coordination in the cartel.
Keywords: L41; K21; C92; 330